Magnetotransport of single crystalline YSb. (10th May 2016) - Ghimire, N J; Botana, A S; Phelan, D; Zheng, H; Mitchell, J F
Abstract: We report magnetic field dependent transport measurements on a single crystal of cubic YSb together with first principles calculations of its electronic structure. The transverse magnetoresistance does not saturate up to 9 T and attains a value of 75 000% at 1.8 K. The Hall coefficient is electron-like at high temperature, changes sign to hole-like between 110 and 50 K, and again becomes electron-like below 50 K. First principles calculations show that YSb is a compensated semimetal with a qualitatively similar electronic structure to that of isostructural LaSb and LaBi, but with larger Fermi surface volume. The measured electron carrier density and Hall mobility calculated at 1.8 K, based on a single band approximation, are 6.5 × 10 20 cm −3 and 6.2 × 10 4 cm 2 Vs −1, respectively. These values are comparable with those reported for LaBi and LaSb. Like LaBi and LaSb, YSb undergoes a magnetic field-induced metal-insulator-like transition below a characteristic temperature T m, with resistivity saturation below 13 K. Thickness dependent electrical resistance measurements show a deviation of the resistance behavior from that expected for a normal metal; however, they do not unambiguously establish surface conduction as the mechanism for the resistivity plateau.